Why Technology Change is Going to get Even Faster. (22nd May 2019) - Glick, Bryan
Abstract: In the last decade, we've been bewildered by new technologies and changes to the way we live and work. But if you want the pace of change to slow down, says Bryan Glick, editor in chief of Computer Weekly you won't be pleased